The Impact of Mental Models on the Transition from Communism to Capitalism. The Comparative Case Study of Azerbaijan and Poland - Pashazade, Nurlan (Journal of Finance and Financial Law, 2024)
The purpose of the article. The breakdown of the so-called Eastern Bloc, the disintegration of the Soviet Union, and the demise of communism fueled transition processes in Central and Eastern Europe, Western Asia, and Central Asia. The great majority of transformation difficulties across different areas demonstrate that when pursuing the process of a structural change, it is important to take into account diverse sets of formal and informal institutions preserved in each country. Each country has a unique set of formal and informal institutions. These differences are easily observed between Poland and Azerbaijan. The aim of this paper is to compare and contrast the outcomes of Poland and Azerbaijan's transitions from communism to capitalism and to identify the primary factors driving these two different transformations.Methodology. The paper presents two complementary methods to compare the transitions from communism to capitalism in Poland and Azerbaijan. The first method involves secondary analysis, where existing data from reputable sources such as the European Bank for Reconstruction and Development (EBRD) database, the Bertelsmann Transformation Index (BTI), and country reports are compiled to provide insights into economic, political, and social indicators. Additionally, a comparative case study approach is employed, using Geert Hofstede's six cultural dimensions framework to explore the cultural influences on transition outcomes. By integrating these methods, the study aims to offer a comprehensive analysis of the transformation processes in Poland and Azerbaijan.Results of the research. The results of the analysis presented in the paper support the hypothesis that the historically-shaped differences in mental models and strong ties to international protectors determined the paths of transformations in Poland and Azerbaijan. The primary similarities and contrasts in the mindset are justified by the colonial or imperial history of the nations.